2000
DOI: 10.1001/archinte.160.12.1862
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Rates of Ischemic Heart Disease in the Native Population of Ontario, Canada

Abstract: Hospitalizations for IHD have doubled in the Native population despite declining rates in the general population. These findings document an alarming trend in Native health and support the need for further research and targeted intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 15 publications
1
63
0
1
Order By: Relevance
“…In a study of dietary intakes of 16 aboriginal communities in the Northwest Territories, Receveur et al (24) found that among Dene and Metis populations there was a shift away from traditional foods to market (14) Macaroni and hamburger helper or ground beef with pasta; Beef burgers; Beef steak; Home-made beef or hamburger stew or soup; Chilli; Roasted, boiled or braised beef; Smoked, roasted or fried moose, caribou or deer (not in soup, stew or stir fry); Boiled, oven-roasted or smoked goose or duck (not in soup, stew or stir fry); Fried chicken, including in sandwich; Chicken nuggets, strips; Grilled, barbecued, roasted or boiled chicken or partridge; Fried, boiled, roasted, braised or broiled pork meat; Bacon; Stir-fry meat with vegetables Fish (5) Canned fish, in oil or tomato sauce; Canned fish, in water; Fried fish (not in soup); Smoked, baked, boiled, broiled or grilled fish (not in soup); Fish, dried Luncheon meats (5) Weiners/hot dogs, breakfast sausages, sausages or smokies; Low-fat hot dogs or sausage; Regular Klik, Prem, Spam, canned ham; Regular lunch meat; Corned beef Rice and pastas (8) Rice with condensed soup, including wild rice casserole; Plain rice (not in soup); Macaroni and cheese or other pasta with cream sauce; Spaghetti, spaghettios with tomato or vegetable sauce; Spaghetti with meat sauce, lasagne; Pizza or pizza pops; Home-made low-fat pizza; Perogies Vegetables (14) French fries or potato wedges; Mashed, scalloped, boiled or baked potatoes; Hash browns, fried potatoes or tater tots; Poutine; Mixed vegetables; Carrots, fresh, canned or frozen; Peas; Green beans; Corn on the cob; Corn, kernels; Potato or macaroni salad, or coleslaw; Salad, garden; Regular salad dressings; Baked beans Fruits (9) Bananas; Apples or pears; Oranges; Melons including watermelon, cantaloupe; Grapes; Plums; Blueberries/ strawberries/raspberries/cherries; Peaches or nectarines, fresh; Fruit cocktail, canned peaches or pineapple Cereals (4) High-sugar cereals; Low-sugar cereals; High-fibre cereals; Porridge/oatmeal Dairy (18) Whole milk in coffee or tea; Whole milk by glass or on cereal; 2 % milk in coffee or tea; 2 % milk by glass or on cereal; 1 % or skimmed milk in coffee or tea; 1 % or skimmed milk by glass or on cereal; Regular evaporated milk in coffee or tea; Regular evaporated milk on cereal; 2 % evaporated milk in coffee or tea; 2 % evaporated milk on cereal; Creamer, half and half, Coffee-mate or other coffee whitener; Low-fat creamer or Coffee-mate; Hard cheese; Milkshake; Yoghurt; Fried, scrambled eggs or omelette; Boiled, poached eggs; Ice cream Sweets (8) Doughnuts, muffins, cup cakes, Danish pastry, cinnamon bun; Cake; Cookies; Low-sugar cookies; Fruit pie, any kind, apple turnover; Popsicles, freezies; Candy, any kind; Chocolate bars or pieces Other foods (13) Chips, any kind; Nuts; Sunflower seeds, with shell; Baked chips; Regular popcorn; Low-fat popcorn; Butter/ margarine; Low-fat spread or margarine; Peanut butter; Artificial sweeteners; Sugar; Gravy; Mayonnaise Beverages (5) Pop/soda, regular; Pop/soda, diet; Fruit cocktail, Tang, Kool-Aid, Five Alive, Sunny Delight, fruit punch, fruit drinks, lemonade, Gatorade, iced tea; 100 % fruit juice; Water Alcohol …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of dietary intakes of 16 aboriginal communities in the Northwest Territories, Receveur et al (24) found that among Dene and Metis populations there was a shift away from traditional foods to market (14) Macaroni and hamburger helper or ground beef with pasta; Beef burgers; Beef steak; Home-made beef or hamburger stew or soup; Chilli; Roasted, boiled or braised beef; Smoked, roasted or fried moose, caribou or deer (not in soup, stew or stir fry); Boiled, oven-roasted or smoked goose or duck (not in soup, stew or stir fry); Fried chicken, including in sandwich; Chicken nuggets, strips; Grilled, barbecued, roasted or boiled chicken or partridge; Fried, boiled, roasted, braised or broiled pork meat; Bacon; Stir-fry meat with vegetables Fish (5) Canned fish, in oil or tomato sauce; Canned fish, in water; Fried fish (not in soup); Smoked, baked, boiled, broiled or grilled fish (not in soup); Fish, dried Luncheon meats (5) Weiners/hot dogs, breakfast sausages, sausages or smokies; Low-fat hot dogs or sausage; Regular Klik, Prem, Spam, canned ham; Regular lunch meat; Corned beef Rice and pastas (8) Rice with condensed soup, including wild rice casserole; Plain rice (not in soup); Macaroni and cheese or other pasta with cream sauce; Spaghetti, spaghettios with tomato or vegetable sauce; Spaghetti with meat sauce, lasagne; Pizza or pizza pops; Home-made low-fat pizza; Perogies Vegetables (14) French fries or potato wedges; Mashed, scalloped, boiled or baked potatoes; Hash browns, fried potatoes or tater tots; Poutine; Mixed vegetables; Carrots, fresh, canned or frozen; Peas; Green beans; Corn on the cob; Corn, kernels; Potato or macaroni salad, or coleslaw; Salad, garden; Regular salad dressings; Baked beans Fruits (9) Bananas; Apples or pears; Oranges; Melons including watermelon, cantaloupe; Grapes; Plums; Blueberries/ strawberries/raspberries/cherries; Peaches or nectarines, fresh; Fruit cocktail, canned peaches or pineapple Cereals (4) High-sugar cereals; Low-sugar cereals; High-fibre cereals; Porridge/oatmeal Dairy (18) Whole milk in coffee or tea; Whole milk by glass or on cereal; 2 % milk in coffee or tea; 2 % milk by glass or on cereal; 1 % or skimmed milk in coffee or tea; 1 % or skimmed milk by glass or on cereal; Regular evaporated milk in coffee or tea; Regular evaporated milk on cereal; 2 % evaporated milk in coffee or tea; 2 % evaporated milk on cereal; Creamer, half and half, Coffee-mate or other coffee whitener; Low-fat creamer or Coffee-mate; Hard cheese; Milkshake; Yoghurt; Fried, scrambled eggs or omelette; Boiled, poached eggs; Ice cream Sweets (8) Doughnuts, muffins, cup cakes, Danish pastry, cinnamon bun; Cake; Cookies; Low-sugar cookies; Fruit pie, any kind, apple turnover; Popsicles, freezies; Candy, any kind; Chocolate bars or pieces Other foods (13) Chips, any kind; Nuts; Sunflower seeds, with shell; Baked chips; Regular popcorn; Low-fat popcorn; Butter/ margarine; Low-fat spread or margarine; Peanut butter; Artificial sweeteners; Sugar; Gravy; Mayonnaise Beverages (5) Pop/soda, regular; Pop/soda, diet; Fruit cocktail, Tang, Kool-Aid, Five Alive, Sunny Delight, fruit punch, fruit drinks, lemonade, Gatorade, iced tea; 100 % fruit juice; Water Alcohol …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CVD is almost three times higher among First Nations than in the general Canadian population (11) . The public health, social and economic impact of the diabetes epidemic in First Nations is tremendous in terms of high rates of CVD, renal failure and retinopathy (5,6,(11)(12)(13)(14) . A diabetes risk factor study conducted in one First Nations community found the age-standardised prevalence of diabetes and impaired glucose tolerance to be 26?1 % and 13?6 %, respectively (15) .…”
mentioning
confidence: 99%
“…These were accompanied by social, economic and cultural changes in the past decades, which might have had an impact on the observed increase in hospitalization for coronary artery disease (50). With the increasing incidence of diabetes that accompanies the transition from traditional to urban lifestyles (51,52), it is anticipated that the incidence of CVD and HF will also increase.…”
Section: The Aboriginal Populationmentioning
confidence: 99%
“…9,12 Among the Native Indian population of the province of Ontario, the rate of hospitalizations for ischemic heart disease has doubled between 1981 and 1997, despite declining rates in the general population. 13 Both the World Health Organization (WHO) and the National Cholesterol Education Program (NCEP) Adult Treatment Panel III have published working definitions of the MetS, [14][15][16][17] and the prevalence rates of the MetS have been assessed in various populations around the world. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, little is known about the distribution of MetS among Aboriginal Canadians.…”
Section: Introductionmentioning
confidence: 99%